EXAMINING RESEARCH-BASED INTERVENTION THAT SUPPORT ACADEMIC SUCCESS FOR DYSLEXIC STUDENTS - Norinboeva Durdonakhon Janobiddin qizi; Olimova Gulasal Fayzullajon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation. Dyslexia is a learning disorder that affects reading, writing, and spelling skills. It is estimated that approximately 10% of the population worldwide has dyslexia, making it crucial to identify effective interventions to support academic success for dyslexic students. Extensive research has been conducted to understand dyslexia and develop evidence-based interventions that can address the specific needs of these students. This article aims to examine some research-based interventions that have shown promising results in supporting academic success for dyslexic students.